2022
DOI: 10.1111/vox.13335
|View full text |Cite
|
Sign up to set email alerts
|

Platelet transfusion and mortality in patients with sepsis‐induced thrombocytopenia: A propensity score matching analysis

Abstract: Thrombocytopenia is common among sepsis patients. Platelet transfusion is frequently administered to increase platelet counts but its clinical impacts remain unclear in sepsis-induced thrombocytopenia. The goal of this study was to explore the association between platelet transfusion and mortality in patients with sepsis-induced thrombocytopenia based on the Medical Information Mart for Intensive Care (MIMIC) III database. In this study, we included 1733 patients with sepsis-induced thrombocytopenia, and these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…No change was noted when clopidogrel–aspirin‐treated platelets were reinfused in mice. This is in line with another study where platelet transfusion did not appear to increase the outcome of sepsis (Wu et al, 2022). Also, we have investigated an LPS‐induced model of inflammation and noted that inflammation was more severe in P2Y 12 deficient mice compared with the control group (Liverani, Kilpatrick, et al, 2014).…”
Section: The P2y12 Receptorsupporting
confidence: 91%
See 1 more Smart Citation
“…No change was noted when clopidogrel–aspirin‐treated platelets were reinfused in mice. This is in line with another study where platelet transfusion did not appear to increase the outcome of sepsis (Wu et al, 2022). Also, we have investigated an LPS‐induced model of inflammation and noted that inflammation was more severe in P2Y 12 deficient mice compared with the control group (Liverani, Kilpatrick, et al, 2014).…”
Section: The P2y12 Receptorsupporting
confidence: 91%
“…The study of Bedet and colleagues was performed on both males and females, but the data were not analysed separately and did not take into account the normally higher platelet count in females. Other studies confirmed that a decrease in platelet production can be one of the causes of thrombocytopenia, but unfortunately, platelet transfusion did not appear to alter the outcome of sepsis (Wu et al, 2022). Moreover, thrombocytopenia has been associated with the presence of autoantibodies against platelets (Aghabeigi et al, 2012), suggesting that platelets may be aggressively phagocyted during sepsis.…”
Section: The Role Of Platelets During Sepsismentioning
confidence: 99%
“…78 This could represent a clearer signal suggesting adverse immune effects can result from liberal platelet transfusion. 128,129 In addition, angiogenic signals may precipitate bleeding during a vulnerable period of neonatal brain development, potentially provided by adult platelets. 130,131 Figure Legend…”
Section: Discussionmentioning
confidence: 99%
“…Poorer outcomes are seen in patients receiving platelet transfusions including significant transfusion reactions such as transfusion-related circulatory overload, transfusionrelated acute lung injury, allergic/anaphylactic reactions, alongside increased nosocomial infections, admission to critical care units, thrombosis, length of stay, and mortality. [3][4][5][6][7][8] Most platelet components are not administered therapeutically for hemorrhage; instead, they are commonly given prophylactically to nonbleeding patients before minimally invasive elective procedures or for various levels of thrombocytopenia not associated with bleeding risk. 9 These prophylactic platelets do not assure the prevention of bleeding and have been associated with increased bleeding episodes in certain clinical scenarios.…”
mentioning
confidence: 99%